2021
DOI: 10.3390/ijerph182111534
|View full text |Cite
|
Sign up to set email alerts
|

Role of SatO2, PaO2/FiO2 Ratio and PaO2 to Predict Adverse Outcome in COVID-19: A Retrospective, Cohort Study

Abstract: COVID-19 respiratory failure is a life-threatening condition. Oxygenation targets were evaluated in a non-ICU setting. In this retrospective, observational study, we enrolled all patients admitted to the University Hospital of Genoa, Italy, between 1 February and 31 May 2020 with an RT-PCR positive for SARS-CoV-2. PaO2, PaO2/FiO2 and SatO2% were collected and analyzed at time 0 and in case of admission, patients who required or not C-PAP (groups A and B) were categorized. Each measurement was correlated to adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 49 publications
0
16
0
2
Order By: Relevance
“…This marker characterizes the potential angiogenic present in COVID-19 samples and its relationship with hypoxia, identified through bedside ventilatory parameters. Evidence has shown that COVID-19 patients are at increased risk of thrombotic events when they have a lower PaO 2 /FiO 2 ratio on admission [ 66 , 67 ]. This highlights the importance of monitoring oxygenation levels in COVID-19 and the potential benefit of using drugs targeting angiogenesis and thrombotic events in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…This marker characterizes the potential angiogenic present in COVID-19 samples and its relationship with hypoxia, identified through bedside ventilatory parameters. Evidence has shown that COVID-19 patients are at increased risk of thrombotic events when they have a lower PaO 2 /FiO 2 ratio on admission [ 66 , 67 ]. This highlights the importance of monitoring oxygenation levels in COVID-19 and the potential benefit of using drugs targeting angiogenesis and thrombotic events in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…LDH is a cytoplasmatic enzymes highly expressed in the lung, liver, hearth, kidney and skeletal muscle, generally release in blood after cell death: thus, the lung damage, frequently founded in COVID-19 postmortem pathology [26] , could increase LDH blood levels [27] . The P/F, a parameters widely used to define the severity of Acute Respiratory Distress Syndrome [28] , has already been shown to be able to predict outcome in patients with COVID-19 [29] , [30] ; moreover, one study highlighted its inverse correlation with extension of the pulmonary inflammatory process on CT [31] .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that a PaO 2 /FiO 2 ratio of less than 300 strongly contributed to poorer outcomes [22]. However, due to severe V/Q mismatch and intrapulmonary shunting caused by COVID-19 involvement, a few studies have suggested nonlinear relations between PaO 2 and FiO 2 [23].…”
Section: Discussionmentioning
confidence: 99%